Effectiveness of Second through Sixth Line Salvage Helicobacter pylori Treatment: Bismuth Quadruple Therapy is Almost Always a Reasonable Choice - Tahir Shaikh; Carlo A. Fallone (Canadian Journal of Gastroenterology and Hepatology)
Aim. There is a paucity of data on the efficacy of empiric H. pylori treatment after multiple treatment failures. The aim of this study is to examine the efficacy of empiric salvage therapy as a second through sixth line treatment. Methods. In this single gastroenterology center prospective study in Montreal, Canada, patients with failed H. pylori treatment were offered empiric salvage therapy based on the patients’ previous antibiotic exposure. Enrollment occurred after 1–5 previous failed attempts and eradication determined at least 4 weeks after completion of treatment. Results. 205 treatments were attempted in 175 patients using 7 different regimens. Eradication was achieved in 154 attempts (PP = 81% (154/191), ITT = 75% (154/205)). Bismuth quadruple therapy (BQT) had higher eradication success (PP = 91% (102/112), ITT = 84% (102/121)) when compared to all PPI triple therapies combined (PP = 66% (49/74), absolute risk reduction (ARR): 25% (95% CI: 13–37), ITT = 62% (49/79), ARR: 22% (95% CI: 10–35), and p<0.001) and when compared to levofloxacin triple therapy (PP = 66% (40/61), ARR: 26% (95% CI: 13–39), ITT = 61% (40/66), and ARR: 24% (95% CI: 10–37)). Eradication was achieved in a high proportion with BQT on attempt two (PP = 94% (67/71), ITT = 91% (67/74)), three (PP = 85% (17/20), ITT = 71% (17/24)), four (PP = 100% (11/11), ITT = 92% (11/12)), and five (PP = 86% (6/7), ITT = 75% (6/8)). Patients with previous combined bismuth and tetracycline exposure had a lower proportion of eradication compared to patients without such an exposure (PP: 60% (6/10) versus 95% (94/99), ARR: 35% (95% CI: 11–64), and p<0.001; ITT: 55% (6/11) versus 90% (94/105), ARR: 35% (95% CI: 10–62), and p<0.01). Conclusions. Salvage therapy with a bismuth quadruple regimen is superior to triple therapies and is effective for second through fifth line empirical treatment (≥85% PP, ≥70% ITT). Successful eradication is significantly lower with BQT if a similar bismuth based regimen was used in the past.